STUDI UJI ALTERNATIF KUALITAS MINYAK GORENG BERDASARKAN PERUBAHAN POLARISASI CAHAYA TERIMBAS - Susan, Ade Ika; Firdausi, K Sofjan; Setiabudi, Wahyu (BERKALA FISIKA, 2011)
AbstractIn this research, we report the quality of several cooking oils before and after heating. The parameter of quality was based on electrooptics characteristic or, so called, the change ofpolarization angle induced by external electric field. In this examination, it was used threedifferent brands of cooking oils. The samples were heated in the time interval between 0-120minutes. The electrooptics characteristic was determined by measuring the change ofpolarization angle of light as it passed through the oil while it was applied by external electricfield. The field was produced by two parallel plates connected to different potential between 0-9kV. The light source was diode laser atλ = 650 nm and λ = 532 nm. The quality of oil was then determined by average polarization angle per potential difference, i.e. α ≡ Δθ/ΔV. Based on the result of observation, the fresh oil before heated has smaller change of polarization angle thanoil after heated, which is in agreement to the previous study. The longer heating time is, morefree radicals are produced, which leads to higher polarization. It shows also that the change ofpolarization depends on the wavelength.  From two diode lasers, the effective wavelength toproduce higher number free radicals is obtained by 532 nm. The increasing average ofpolarization angle is linearly to the increasing of heating time. It is obvious that the electroopticsparameter could be proposed as an alternative quality test of cooking oil.Keyword: Cooking oil quality, Change of polarization angle, electrooptics